The Relationship Between Residential Distance and the Utilization of Midwifery Services Among Pregnant Women - Kintan Anissa; Nimas Ayu Lestari Nurjanah (Minsight: Midwifery Insight and Innovation Journal, 2026)
This study aimed to analyze the relationship between residential distance and the utilization of midwifery services among pregnant women. Access to maternal health services remains an important factor influencing the quality of antenatal care, particularly in areas with limited transportation and health facilities. This research employed a quantitative analytic design with a cross-sectional approach. The study population consisted of pregnant women who attended maternal health services at selected healthcare facilities. Data were collected using structured questionnaires and analyzed using statistical tests to determine the association between residential distance and the utilization of midwifery services. The results showed that pregnant women living closer to healthcare facilities were more likely to utilize midwifery services regularly compared to those living farther away. Distance was identified as a significant factor affecting the frequency of antenatal visits and access to skilled maternal healthcare. In addition, transportation availability and socioeconomic conditions also influenced service utilization. The findings imply that improving accessibility to maternal healthcare services, including transportation support and equitable distribution of midwifery facilities, may increase the utilization of antenatal care among pregnant women and contribute to better maternal and fetal health outcomes.